Investigation of the appearance and elimination of pinking coloration in white wines - Bilko, Marina; Gunko, Sergiy; Babich, Irina; Naumenko, Oksana; Mukoid, Roman; Ischenko, Mykola; Doboniy, Inna; Danylenko, Svetlana; Bovkun, Alla; Stotska, Olena (My University, 2022)
Investigation of the appear¬ance and elimination of “pinking” phenomenon in white wines is pre¬sented in the paper. Several factors that can cause pinking were ana¬lyzed: the degree of grapes ripeness and enzymatic treatment. The effect of fining agents based on polyvin¬ylpolypyrrolidone (PVPP) on the elimination of “pinking” was deter¬mined. It was proved that pinking in wines decreases with an increase in the sugar content in grape. This is explained by a decrease in the content of anthocyanins at the end of technical ripeness of grape. Experimental studies confirmed that the use of pectolytic enzymes with cellulase, hemicellulase, β-glucanase activities increases the intensity of straw color and the appearance of body tones, but does not affect pinking. Such treatment contributed to a slight increase in the content of phenolic compounds in wine materials, but did not affect the content of anthocyanins and “pinking” susceptibility. Treatment of wine materials with complex PVPP-based agents including sor¬bents and flocculants, is an effec¬tive way to eliminate the “pink¬ing” phenomenon. This reduces “pinking” in wine materials from 70…90 % to 1…2 %. This is due to the presence of sorbents and floc¬culants in the fining agents, which react with phenolic substances that cause “pinking” in white wines, and remove them from the system. So, there are reasons to argue that processing grape at the end of tech¬nical ripeness will contribute to a lower “pinking” susceptibility of wine materials; pectolytic enzymes did not affect the appearance of this phenomenon in white wines, and PVPP-based fining agents together with bentonite, activated carbon, gelatin or casein, are an effective way to reduce the “pinking” sus¬ceptibility of wine.

У статті представлено дослідження виникнення та усунення явища «порожіння» у білих винах. Проаналізовано кілька факторів, які можуть спричинити порозовіння: ступінь стиглості винограду та ферментативну обробку. Визначено вплив освітлювачів на основі полівінілполіпіролідону (ПВПП) на усунення «розовіння». Доведено, що рожевість вин зменшується зі збільшенням вмісту цукру у винограді. Це пояснюється зниженням вмісту антоціанів у кінці технічної стиглості винограду. Експериментальними дослідженнями підтверджено, що застосування пектолітичних ферментів з целюлазною, геміцелюлазною, β-глюканазною активністю підвищує інтенсивність солом’яного кольору та появу тілесних відтінків, але не впливає на рожевість. Така обробка сприяла незначному збільшенню вмісту фенольних сполук у виноматеріалах, але не впливала на вміст антоціанів і сприйнятливість до «розовіння». Обробка виноматеріалів комплексними препаратами на основі ПВПП, у тому числі сорбентами та флокулянтами, є ефективним способом усунення явища «порозовіння». Це знижує «розовесть» виноматеріалів з 70…90 % до 1…2 %. Це пов’язано з наявністю в освітлювачах сорбентів і флокулянтів, які вступають в реакцію з фенольними речовинами, що викликають «розовіння» білих вин, і видаляють їх із системи. Отже, є підстави стверджувати, що переробка винограду в кінці технічної стиглості сприятиме меншій сприйнятливості до «розовення» виноматеріалів; пектолітичні ферменти не вплинули на появу цього явища в білих винах, а освітлювачі на основі PVPP разом з бентонітом, активованим вугіллям, желатином або казеїном є ефективним засобом зниження сприйнятливості вина до «розовіння».
Keywords: кафедра біотехнології продуктів бродіння і виноробства; “pinking”; white wines; grape ripeness; enzymes; polyvinylpolypyrrolidone; phenolic substances; anthocyanins; білі вина; стиглість винограду; ферменти; полівінілполіпіролідон; фенол речовини; антоціани